Moderating Role of Perceived Social Support in the Relationship Between Emotion Regulation and Quality of Life in Chinese Ocean-Going Fishermen - Wu, Yongmei; Li, Sailan; Yang, Juan (Frontiers in Psychology, 2020)
Perceived social support (PSS) has been shown to be positively related to self-reported quality of life (QoL) as well as to emotion regulation strategy. In the present study, we compared a QoL index between Chinese fishermen (N = 507) and local villagers (N = 192), and examined whether PSS moderates the relationship between emotion regulation and QoL in our sample of Chinese ocean-going fishermen. Fishermen’s QoL was found to be poorer than that of local villagers. Structural equation modeling (SEM) confirmed that cognitive reappraisal of emotion regulation had a positive predictive effect on QoL, while expression suppression of emotion regulation had a negative predictive effect on QoL. Using, latent moderated structural equations (LMS), we further confirmed that PSS moderates the relationship between emotion regulation and QoL. Simple slope analysis revealed that emotional regulation can predict QoL in a high-PSS context, but not in a low-PSS context.